2015
DOI: 10.3389/fnbeh.2015.00148
|View full text |Cite
|
Sign up to set email alerts
|

fMRI neurofeedback facilitates anxiety regulation in females with spider phobia

Abstract: Background: Spider phobics show an exaggerated fear response when encountering spiders. This fear response is aggravated by negative and irrational beliefs about the feared object. Cognitive reappraisal can target these beliefs, and therefore has a fear regulating effect. The presented study investigated if neurofeedback derived from functional magnetic resonance imaging (fMRI) would facilitate anxiety regulation by cognitive reappraisal, using spider phobia as a model of anxiety disorders. Feedback was provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
126
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 115 publications
(126 citation statements)
references
References 63 publications
0
126
0
Order By: Relevance
“…Within this context, the emergence of real-time functional magnetic resonance imaging neurofeedback (rt-fMRI NF) training (NFT) approaches that allow subjects to gain volitional control over regional brain activity have been considered as a putatively promising strategy [28-30]. Importantly, previous studies have confirmed this potential of rt-fMRI NF by demonstrating that training success in terms of control over regional activity can be maintained beyond the training session [31-34], and that training-induced neural activity changes can modulate emotional experience in healthy subjects [31] and patients with major depression [32-35]. …”
Section: Introductionmentioning
confidence: 74%
“…Within this context, the emergence of real-time functional magnetic resonance imaging neurofeedback (rt-fMRI NF) training (NFT) approaches that allow subjects to gain volitional control over regional brain activity have been considered as a putatively promising strategy [28-30]. Importantly, previous studies have confirmed this potential of rt-fMRI NF by demonstrating that training success in terms of control over regional activity can be maintained beyond the training session [31-34], and that training-induced neural activity changes can modulate emotional experience in healthy subjects [31] and patients with major depression [32-35]. …”
Section: Introductionmentioning
confidence: 74%
“…Instructions were minimal (i.e., “you can try to concentrate on the rocket” or “try any other method that works for you”) as this has been shown to be more effective than explicit instructions [Sulzer et al, 2013], and instruction‐free approaches are common in EEG‐NF for ADHD children [Gevensleben et al, 2014; Strehl et al, 2006]. However, in rtfMRI‐NF it has been shown that for some regions it appears to make no difference whether instructions are given (e.g., motor regions [Sepulveda et al, 2016]), while explicit instructions may be beneficial for the self‐regulation of specific brain areas (e.g., limbic system [Zilverstand et al, 2015]. They received continuous feedback (every repetition time (TR), i.e., 2 s), about their brain activation in their target region of interest (ROI) via the rocket video‐clip, with the direction and distance travelled in space proportional to their BOLD response.…”
Section: Methodsmentioning
confidence: 99%
“…Studies in psychiatric/neurological disorders highlight the clinical potential of rtfMRI‐NF [Thibault et al, 2015, 2016], showing generalization to NF‐free transfer runs and longer‐term beneficial effects of up to several months [Zilverstand et al, 2015]. Importantly, by learning to self‐upregulate isolated regions, participants learn to co‐regulate other areas interconnected with the target region, suggesting modulation of entire networks [Emmert et al, 2016; Thibault et al, 2016].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, looking across experiments we find many cases of distinct protocols encouraging regulation in opposing directions. For example, many experiments train participants to up-regulate anterior insular activity to increase valence ratings (Caria, Sitaram, Veit, Begliomini, & Birbaumer, 2010;Lawrence et al, 2014;Ruiz et al, 2013;Sitaram et al, 2014), while other studies encourage down-regulation to decrease pain perception (Emmert et al, 2014;Rance, Ruttorf, Nees, Rudi Schad, & Flor, 2014) or subdue a phobia (Zilverstand, Sorger, Sarkheil, & Goebel, 2015).…”
Section: Future Stepsmentioning
confidence: 99%